KONSTRUKSI IDENTITAS KEISLAMAN KESULTANAN BACAN MELALUI RITUAL TOLAK BALAK - Flavius Floris Andries (TANGKOLEH PUTAI, 2021)
The issue of identity becomes an interesting thing to discuss because identity is always phenomenal. Specifically, the identity problem discussed in this article is the construction of the Islamic identity of the Bacan Sultanate through the ritual of rejecting Balak. This research was conducted on the grounds that this ritual is a ritual that has an Islamic spirit but opens up space for non-Muslim communities to participate in it. Research questions that arise from this problem include: 1). How is the history and growth of Islam in the Bacan Sultanate? 2). How was the ritual process and what was its impact in relation to the multicultural facts of the people of the Bacan Sultanate? This research was conducted using qualitative methods with interview, observation and literature studies. The results of the study found that: 1). The exclusive and inclusive identity of the people of the Bacan sultanate is constructed through the ritual of rejection of balance, showing that identity is never static, but always dynamic or liquid. 2) The existence of dynamics in the process of identity construction as seen in the ritual of back and forth from the inclusive back to the exclusive emphasizes Berger firmly about the dialectic process in the construction of social identity (1994:4). 3). religion has a double face or has an ambiguous nature. The dimension of prayer in ritual is a means of exclusion and at the same time confirms the ambiguity of religion itself.